1995
DOI: 10.1111/j.1440-1681.1995.tb02060.x
|View full text |Cite
|
Sign up to set email alerts
|

REPAIR AND RECOVERY FOLLOWING SPINAL CORD INJURY IN A NEONATAL MARSUPIAL (MONODELPHIS DOMESTICA)

Abstract: 1. Repair and recovery following spinal cord injury (complete spinal cord crush) has been studied in vitro in neonatal opossum (Monodelphis domestica), fetal rat and in vivo in neonatal opossum. 2. Crush injury of the cultured spinal cord of isolated entire central nervous system (CNS) of neonatal opossum (P4-10) or fetal rats (E15-E16) was followed by profuse growth of fibres and recovery of conduction of impulses through the crush. Previous studies of injured immature mammalian spinal cord have described fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 25 publications
3
43
0
Order By: Relevance
“…Indeed, we found that, in the absence of both IF proteins, astrocytes were morphologically immature (16,25). It is well known that, in the immature CNS, regenerating fibers can grow through lesions (26). This phenomenon seems to be due in part to decreased glial scar formation, thus creating a permissive environment for axonal regeneration (27).…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, we found that, in the absence of both IF proteins, astrocytes were morphologically immature (16,25). It is well known that, in the immature CNS, regenerating fibers can grow through lesions (26). This phenomenon seems to be due in part to decreased glial scar formation, thus creating a permissive environment for axonal regeneration (27).…”
Section: Discussionmentioning
confidence: 67%
“…Another of the more exciting developmental models of SCI was developed by an Australian group led by Dr Norman Saunders and has been used extensively to study the unique capacity of the immature spinal cord to regenerate after SCI (37). In this model, the neonatal opossum, Monodelphis domestica, undergoes complete spinal cord transection by a microscalpel in the midthoracic region (T4-T6).…”
Section: Review Of Animal Modelsmentioning
confidence: 99%
“…The exact time at which regeneration ceases varies from species to species (1)(2)(3)(4)6) and within an animal, depending on the maturity of the tract that has been disrupted (7)(8)(9)33). Eventually all CNS regeneration fails except in the olfactory system.…”
mentioning
confidence: 99%